Assessments of Masonry Buildings and Historical Structures during the 2020 Sivrice-Elazığ Earthquake - Özmen, Alper; Maraş, Müslüm Murat; Ayaz, Yaşar; Sayın, Erkut (Periodica Polytechnica Civil Engineering, 2023)
Turkey is located on a seismically active region. The active fault zones, primarily the North Anatolian Fault and East Anatolian Fault, constitute a center to the movements. On 24 January 2020 at local time 20:55, an earthquake of Mw = 6.8 struck Sivrice, Elazığ located in eastern part of Turkey. After this main shock, 1185 aftershocks were recorded until February 8, 2020. The main event resulted in 41 human casualties and 1632 injured. Also, 45 people were salvaged from the debris. The earthquake mostly affected to Elazığ and Malatya provinces. 633 buildings were demolished, 10492 buildings were severely damaged, 2161 buildings were moderately damaged, and 16046 buildings were slightly damaged in the affected region. This paper focus on evaluating the damages and failures of masonry, adobe, and historical structures in the affected areas around Elazığ and Malatya provinces.